Upaya Meningkatkan Minat Belajar Siswa Kelas 8c Dalam Pendidikan Agama Kristen Melalui Strategi Pembelajaran Berbasis Masalah Di Sekolah Menengah Pertama BOPKRI 3 Yogyakarta - Intan Anggreni; Ester Agustini Tandana; Eko Basuki; Liantoro Liantoro; Lionarto Erson Jayadi (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2024)
This study aims to improve the learning interest of class 8C students in the subject of Christian Religious Education at SMP BOPKRI 3 Yogyakarta through the implementation of Problem-Based Learning (PBL) strategies. The research method used is classroom action research (CAR) which consists of several cycles, each covering the stages of planning, implementation, observation, and reflection. The results of the study indicate that the implementation of PBL is effective in improving students' learning interest. Students are more actively involved in the learning process, show improvements in critical thinking skills, and are more enthusiastic in solving problems related to the subject matter. This improvement is reflected in better academic grades and student activity during the learning process. In addition, supporting factors such as teacher support in guiding discussions, the use of interesting learning media, and a conducive classroom atmosphere also contribute to increasing students' learning interest. This study is that the Problem-Based Learning strategy is effective in improving the learning interest of class 8C students in Christian Religious Education. Recommendations for further research are to adopt PBL in other subjects and expand the use of learning media to further increase student engagement and interest in learning. Keywords: Learning interest, Christian Religious Education, Problem-Based Learning (PBL), classroom action research, junior high school students. Penelitian ini bertujuan untuk meningkatkan minat belajar siswa kelas 8C dalam mata pelajaran Pendidikan Agama Kristen di SMP BOPKRI 3 Yogyakarta melalui penerapan strategi Pembelajaran Berbasis Masalah (PBM). Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK) yang terdiri dari beberapa siklus, masing-masing mencakup tahap perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa penerapan PBM efektif dalam meningkatkan minat belajar siswa. Siswa lebih aktif terlibat dalam proses pembelajaran, menunjukkan peningkatan dalam kemampuan berpikir kritis, dan lebih antusias dalam menyelesaikan masalah yang berkaitan dengan materi pelajaran. Peningkatan ini tercermin dalam nilai akademik yang lebih baik dan keaktifan siswa selama proses pembelajaran. Selain itu, faktor-faktor pendukung seperti dukungan guru dalam membimbing diskusi, penggunaan media pembelajaran yang menarik, dan suasana kelas yang kondusif juga berkontribusi terhadap peningkatan minat belajar siswa. Penelitian ini adalah bahwa strategi Pembelajaran Berbasis Masalah efektif dalam meningkatkan minat belajar siswa kelas 8C dalam Pendidikan Agama Kristen. Rekomendasi untuk penelitian selanjutnya adalah mengadopsi PBM dalam mata pelajaran lain dan memperluas penggunaan media pembelajaran untuk lebih meningkatkan keterlibatan dan minat belajar siswa.